Simulation-Assisted Instruction on Electro-Thermal Relationships in Metal-Oxide Varistors Using the FDTD Method - Fauzan, Muhammad Farrel Dava; Siffa, Nur; Pratiwi, Fita; Fadilah, Okan; Azizah, Defi Rosiana (MJI Publisher by PT Mitra Jurnal Indonesia, 2025)
Metal-Oxide Varistor (MOV) is a key component in electrical protection systems, safeguarding devices from excessive voltage surges. MOV exhibits non-linear behavior, acting as an insulator at normal voltages and a conductor at high voltages, absorbing excess energy to protect connected devices. This study employs the Finite-Difference Time-Domain (FDTD) method to analyze the electro-thermal characteristics of MOV, including the voltage-current relationship, resistivity changes with temperature, and temperature distribution within MOV. The FDTD method models the distribution of electric fields, magnetic fields, and temperature within MOV, which is modeled as small rectangular elements with resistivity dependent on the local electric field and temperature. Temperature distribution is calculated using the heat transfer equation, with resistivity determined based on experimental measurement data. Visualizations include graphs of the electric field and resistivity relationship at various temperatures and temperature distribution maps. Simulation results show that the Gaussian impulse current wave generates significant voltage surges and uneven temperature distribution within MOV. Above 600 K, the material's resistivity significantly decreases, allowing larger currents to flow through MOV. Temperature distribution in the form of heat maps identifies hotspots that may cause local degradation of MOV. These findings provide crucial insights for the design and analysis of overcurrent protection in electrical devices, ensuring the effectiveness of MOV in protecting devices from excessive voltage surges.